Walking Tour sebagai Media Interpretasi Warisan Budaya Palembang Integrasi Situs Lokal dan Kolonial - Tri Artika Murtiani Putri; Syarifuddin; Alif Bahtiar Pamulaan (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
This study aims to analyze the effectiveness of walking tours as an interpretation medium in integrating local and colonial cultural heritage in Palembang. The research method uses a qualitative approach through the implementation of a walking tour attended by ten Tourism students. The route includes Talang Keranggo Cemetery, Ki Ronggo Wiransentiko Cemetery, colonial buildings along Talang Semut, and ends at Kambang Iwak. Data were collected through participatory observation, in-depth interviews, and visual documentation. Data were analyzed thematically using an interpretive approach. The results show that the walking tour not only strengthened participants’ understanding of the historical value of each site but also created an integrative narrative between local and colonial heritage. Participants were able to identify symbolic and functional relationships between the sites within the context of Palembang’s urban development. The walking tour proved effective as an interactive, contextual medium for heritage education. It is concluded that this approach can be developed as an experience-based heritage interpretation model. Suggestions for further research include developing routes that integrate augmented reality to enhance interpretive experiences.